Dark tourism development in a leisure destination: the perceptions of the local community in Cyprus - Panayidou, Chryso; Christou, Prokopis A.; Saveriades, Alexis (My University, 2024)
The aim of this exploratory study was to increase the understanding of the perceptions of local communities of dark tourism development in a leisure destination and whether their perceptions could have an impact on the further development or hindrance of dark sites. Cyprus was used as a focal point for the study, an island that is a popular holiday destination but nonetheless has its share of locations and sites related to dark tourism. Social exchange theory was used as a theoretical instrument to examine the local communities’ perceptions. Qualitative research was conducted with three study groups using interviews. It used thematic analysis to identify various themes associated with dark tourism based on the perceptions of the local community. Only a little evidence was found that the concept of dark tourism plays a role in the tourism industry in a leisure destination. The overall positive shared perceptions encourage support for the development of dark tourism; thus, it points to the need to find ways to align future policies with the perceptions and opinions of the local community. This study contributed to knowledge by conceptualizing the role of local communities in dark tourism development.
Keywords: Dark tourism development; leisure destination‌; local community; perceptions